Ethiopia Social Accounting Matrix (SAM), 2005-06 - Ethiopian Development Research Institute; University of Sussex; International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Ethiopia Social Accounting Matrix (SAM), 2005-06 provides a coherent and detailed database on production, income, consumption, investment, external trade and other flows in the economy. The SAM distinguishes 42 production activities, 61 commodity groups, 5 primary factors, 2 household groups, 17 tax instruments as well as aggregate accounts for trade margins, transport margins, government, investment, and the rest of the world.